Financial, accounting-analytical support and management of economic security in the system of sustainable development - Shmatkovska, Tetiana; Derevianko, Svitlana; Rogach, Svitlana; Shulha, Olha; Chudovets, Vitali; Artemchuk, Liudmyla; Begun, Svitlana; Khomiuk, Nataliia (My University, 2023)
The article considers the issues of financial and analytical support and management of economic security in the context of sustainable development. The key aspects of the relationship between financial indicators, analytical tools, and strategies for ensuring sustainable growth are analyzed. The importance of using effective financial monitoring to identify and prevent economic threats is proven. The objective necessity of ensuring the integration of financial and analytical approaches into the process of economic security management to achieve theeffectiveness of sustainable development is determined. The use of elements of strategic management of financial security in the process of forming integrated strategies for sustainable development is recommended.
Keywords: financial monitoring; analysis of indicators; strategic management; economic threats; sustainable development